Anti-inflammatory and immuno-modulatory studies on LC-MS characterised methanol extract of Gentiana kurroo Royle. Issue 1 (December 2017) - Mubashir, Khan; Ganai, Bashir; Ghazanfar, Khalid; Akbar, Seema; Rah, Bilal; Tantry, Mudasir; Masood, Akbar
Abstract Background In ayurvedic traditional medicineGentiana kurroo Royle (family;Gentianaceae ) is used to treat several metabolic diseases. This plant is rich in various compounds belonging to flavonoids and glycosides. Till now little work has been carried out on immunomodulatory and anti-inflammatory potential of this plant. This study confirms the presence of bioactive compounds and evaluates the anti-inflammatory and immunomodulatory effect of this plant. Methods To carry out this work, the methanol extract was investigated in different doses using in vivo and in vitro models. In vivo study involved haemagglutination titre and DTH methods, and in vitro study was done using splenocyte proliferation assay and LPS stimulated macrophage culture. TNF-α, IL-6 and NO were assayed using ELISA kit methods, while NF-κ B was evaluated by western blotting. LC-ESI-MS/MS was used for the characterization of the methanol extract. Results The results showed suppression of both humoral and cell mediated immunity in vivo. This effect was also observed by inhibition of B and T cell proliferation in splenocyte proliferation assay. TNF-α, IL-6 and NO concentrations were also less in extract treated macrophage cultures. The NF-κ B expression was also lowered in treated macrophages as compared to untreated macrophages. All these observations were found to be dose dependent. LC-MS characterization of this extract showed the presence of known compounds which are glycosides, alkaloids and flavonoids in nature. Conclusion The methanol extract of this plant was found to be rich in glycoside, alkaloid and flavonoid compounds. These compounds are probably responsible for the suppression of immune response and anti-inflammatory activity. The extract as such and identified bioactive compounds can be useful for the treatment of inflammatory disorders.